Environmental Risk Factors and Spatial Distribution of Pulmonary Tuberculosis in Tanjung Morawa, Indonesia - Desy Ari Apsari; Deli Syaputri; Samuel Marganda H Manalu; Susanti Br Perangin-angin (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Pulmonary tuberculosis remains a major public health issue, particularly in regions with poor living conditions that facilitate transmission. Understanding the interplay between environmental risk factors and spatial distribution is essential for designing effective interventions. This study examined environmental determinants and spatial clustering of pulmonary tuberculosis cases within the Tanjung Morawa Health Center area, Deli Serdang Regency, Indonesia. Using an observational analytic case-control design, 160 respondents (80 cases and 80 controls) were selected through simple random sampling. Environmental data, including ventilation, humidity, lighting, residential density, floor condition, and wall condition, were collected through systematic observation and direct measurement. Statistical analyses employed Chi-square tests and multiple logistic regression, whilespatial analysis utilized Geographic Information System (GIS) methods, including Average Nearest Neighbor, overlay, and buffer analyses. Results revealed that household humidity was the strongest predictor of pulmonary tuberculosis (OR=44.33), followed by inadequate lighting and poor floor conditions. Ventilation, wall quality, and residential density showed no significant associations. Spatial analysis demonstrated a clustered distribution pattern, indicating localized transmission in high-risk areas. These findings highlight the critical role of housing quality in tuberculosis transmission.  Targeted interventions focusing on humidity control, housing improvements, and environmental health promotion are recommended to reduce disease burden in identified clusters Keywords: Tuberculosis, Spatial Distribution Pattern, Environmental Risk Factors, Housing Quality